From Limited Means to Rising Affluence: How Income Transition Influence Gen Z’s Clothing and Food Purchase Intentions - indrajit, indrajit (12th International Scholars Conference 2025, 2026)
This study investigates how income transition influences Generation Z’s purchase intentions across two essential consumption categories: clothing and food. Drawing on qualitative data from 218 respondents in North Sulawesi, Indonesia, the research captures how Gen Z’s motivations evolve between their current student life with limited resources and their anticipated future as financially independent earners. Using thematic analysis, open-ended responses were categorized into drivers such as price-consciousness, comfort/quality, prestige/brand image, cultural familiarity, and exploration/curiosity. Findings reveal that clothing purchase intentions shift more dramatically than food as income rises. As students, Gen Z predominantly favors local clothing brands due to affordability and comfort, while in the future, their preferences expand toward branded and foreign labels driven by prestige and aspirational motives. In contrast, food purchase intentions display stronger continuity: local foods dominate due to cultural familiarity and taste, though increased income fosters curiosity for foreign cuisines.